Intelligent quantitative assessment on the spray performance of alternative aviation fuel - Liu, Ziyu; Wang, Zhichao; Gu, Xiaoyu; Liu, Haobo; Yang, Luhua; Yang, Jingying; Yang, Xiaoyi (Frontiers in Energy Research, 2022)
Drop-in alternative aviation fuel as a blend of petroleum derived kerosene with sustainable jet fuel has the advantage in CO2 reduction and can be used without any modifications to the engine and aircraft. Therefore, alternative aviation fuel blend as drop-in could not scarify the performance than traditional jet fuel. For assessing the spray performance quantitatively traditional jet fuel (RP-3) with blend alternative compositions including paraffins, cycloparaffins, aromatics were designed to investigate the spray performance from the view of carbon number distribution and classification distribution in jet fuel compositions. Cone angle and liquid length are recognized by shadow image while SMD and velocity are investigated by PDA. The liquid lengths and droplet size of bicyclohexane, phenyl-cyclohexane, and heptadecane, octadecane conduct the significant deviation compared with RP-3, which comply with the large deviations of Lb (f) [σ^0.25 μ_f^0.25 ρ_f^0.25 ] extracted the fuel properties item from liquid length and Oh(f) [ μ_f σ^(-0.5) ρ_f^(-0.5)] extracted the fuel properties item from Ohnesorge number. The blend fuels of those cannot certify as drop-in fuel due to obvious deviation to RP-3, which also present deviation in carbon number distribution and classification distribution. The spray empirical models have been established quantitatively to assess the characteristics of liquid sheet and droplet for discovering the blend fuel effects. The empirical equations of liquid length and SMD calibrated by evaporation constants can agree well with the experimental data except blends of bicyclohexane, phenyl-cyclohexane, C17, C18. The integrated spray performance assessment models developed could benefit for certifying drop-in fuel at spray level quantitatively.